Tono léxico y estructura métrica de la palabra amahuaca: hacia una comprensión de los patrones prosódicos de una lengua pano de las cabeceras - Zariquiey, Roberto (2024)
In the prosody of the Amahuaca language (Pano, Peru), we identify a lexical tone that contrasts with the absence of tone (H vs. Ø) and a metric structure based on the formation of trochaic feet from left to right. These features interact in such a way that the tonal structure of the roots changes in morphologically complex words, preventing high tones from falling on even, non-prominent syllables. Although the lexical tone of Amahuaca roots can be classified as a tonal system, the metric structure of the word would not satisfy the principle of culminativity, which assumes the presence of a syllable with maximum prosodic prominence (primary stress) in words with two or more well-formed metric feet.